Avaliação das alterações moleculares dos folículos dentários em relação à idade cronológica - Vinicius Cesar Barbosa de Menezes (2020)
The dental follicle (DF) is a tissue of ectomesenquimal origin. Approximately 57 % of young adults have impacted third molars, which is the most prevalent impacted tooth. The incidence of pathological changes is greater among older individuals than younger individuals. However, the mechanisms behind the formation of cysts and tumors related to DFs have not been fully clarified and, therefore, some researchers defend the prophylactic extraction of third molars. During chronological aging, epigenetic patterns change and a global DNA hypomethylation pattern can be found concomitantly with hypermethylation of several tumor suppressor genes. DNA methylation is one of the regulators of cell signaling pathways, such as the MAPK/ERK pathway. Some researchers have found an increase in ERK1/2 activity during the aging process, which may contribute to the occurrence of disease, and its dysregulation is involved in the induction and progression of diseases such as cancer and autoimmune diseases. Thus, the aim of the present study was to evaluate whether DFs in young and older individuals differ in terms of global methylation and hydroxymethylation and to evaluate the immunoexpression pattern of phosphorylated ERK1/2. Global DNA methylation (5mC content) and hydroxymethylation (5hmC) were evaluated by ELISA in 59 DF samples We tested the correlation between 5mC and 5hmC content, and the correlation of each with patients’ age. We examined ERK1/2 immunoreactivity for the evaluation of the activation of the MAPK pathways in 46 DF samples. Age of patients of the 59 samples of DFs raged from 13 to 31 years. An inversely proportional relation was found between the 5hmC content and age up to 19 years, therefore, the percentage of 5hmC in the DFs tends linearly decrease with aging. The immunohistochemical study showed a variable pattern of immunoexpression of pERK 1/2 with 46% (21/46) of the samples showing less than 10% of positive cells, while 24% (11/46) of the samples showed immunopositivity between 10 and 50% and 30% (14/46) of the samples greater than 50% of the DF cells. There was no difference in age among these groups. In conclusion, our results suggest that the global hydroxymethylation of DNA changes in its pattern during aging and that the MAPK/ERK cell signaling pathway is active in DFs.